Does low inflation pose a risk to economic growth and central banks reputation? - Marek Dabrowski (Center for Social and Economic Research (CASE), 2020)
Inflation in advanced economies is low by historical standards but there is no threat of deflation. Slower economic growth is caused by supply-side constraints rather than low inflation. Below-the-target inflation does not damage the reputation of central banks. Thus, central banks should not try to bring inflation back to the targeted level of 2%. Rather, they should revise the inflation target downwards and publicly explain the rationale for such a move. Risks to the independence of central banks come from their additional mandates (beyond price stability) and populist politics.
Keywords: E31; E51; E52; E58; F62; 330; monetary policy; inflation; inflation target; economic growth; central bank independence